The Punitive Imagination : Law, Justice, and Responsibility - Sarat, Austin (Book collections on Project MUSE., 2014)
From the Gospel of Matthew to numerous US Supreme Court justices, many literary and legal sources have observed that how a society metes out punishment reveals core truths about its character. The Punitive Imagination is a collection of essays that engages and contributes to debates about the purposes and meanings of punishment in the United States. The Punitive Imagination examines some of the critical assumptions that frame America''s approach to punishment. It explores questions such as:· What is the place of concern for human dignity in our prevailing ideologies of punishment?·